The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.51248/.v42i4.1696
|View full text |Cite
|
Sign up to set email alerts
|

Compound odontomas – A roadblock to tooth eruption and shedding: A case series

Abstract: The most prevalent type of odontogenic tumours are odontomas, which are typically asymptomatic. This study describes three cases of compound odontomas identified in children as a result of dislodgement or over-retention of primary anterior teeth and/or swelling of the cortical bone. In each of these situations, the lesions were surgically excised. The outcomes obtained show that an early detection of odontomas enables the use of a less expensive and complex treatment and ensures a better prognosis. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Pratima., et al (2022) reported three series of compound odontoma cases in their study, which were treated conservatively by surgery with enucleation, resulting in good outcomes. 16,17…”
Section: Discussionmentioning
confidence: 99%
“…Pratima., et al (2022) reported three series of compound odontoma cases in their study, which were treated conservatively by surgery with enucleation, resulting in good outcomes. 16,17…”
Section: Discussionmentioning
confidence: 99%